2010
DOI: 10.1007/s10165-010-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept response in patients with rheumatoid arthritis after secondary loss of efficacy of infliximab

Abstract: This study was carried out to determine the effectiveness of half-dose administration of etanercept in patients with rheumatoid arthritis (RA) who exhibited secondary loss of efficacy of infliximab. Seventeen patients were administered 25 mg of etanercept once weekly for at least 1 year after secondary loss of efficacy of infliximab. The mean duration of treatment with infliximab was 32.5 ± 1.3 months. The patient cohort consisted of 3 males and 14 females, with a mean age of 56.3 ± 11.4 years and mean weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…An important problem associated with the use of infliximab, however, is that its efficacy often decreases during prolonged treatment. It has been reported that switching from infliximab to etanercept was effective in RA patients [9,10,13]. Although both these drugs bind to TNF a, etanercept also binds to lymphotoxin-alpha (previously known as TNF-beta) [9]; this explains why the switch can be effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important problem associated with the use of infliximab, however, is that its efficacy often decreases during prolonged treatment. It has been reported that switching from infliximab to etanercept was effective in RA patients [9,10,13]. Although both these drugs bind to TNF a, etanercept also binds to lymphotoxin-alpha (previously known as TNF-beta) [9]; this explains why the switch can be effective.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important problem associated with the use of infliximab in therapeutic drug regimens is that its efficacy often decreases during prolonged treatment. Some patients who experience treatment failure with their initial agent may benefit from a therapeutic switch from one TNF antagonist to another [9][10][11][12][13]. Indeed, there are now numerous reports that have suggested that initiating therapy with a second anti-TNF a agent in patients who have failed therapy with a first agent may be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…One is the absence of any clinical response (primary lack of efficacy); the other is the disappearance of an initial favorable response during therapy (secondary loss of efficacy). It has been suggested that switching to an alternative anti-TNFα agent may be less effective in nonresponders who showed a primary lack of efficacy than in those in whom the first anti-TNFα agent was withdrawn due to a secondary loss of efficacy [79]. To date, however, we lack reliable guidelines for choosing alternative treatments for individual RA patients who fail to respond to their first anti-TNFα agent [10, 11].…”
Section: Introductionmentioning
confidence: 99%